Compressed-natural-gas optimised downsized demonstrator engine. (January 2018) - Hall, Jonathan; Hibberd, Benjamin; Streng, Simon; Bassett, Michael
The complexity of modern powertrain development is demonstrated by the combination of requirements to meet future emission regulations and test procedures such as the real driving emissions, the reductions in the fuel consumption and the carbon dioxide emissions as well as the expectations of customers that there must be a good driving performance. Gasoline engine downsizing is already established as a proved technology to reduce the carbon dioxide emissions of automotive fleets. Additionally, alternative fuels such as natural gas offer the potential to reduce significantly both the tailpipe carbon dioxide emissions and the other regulated exhaust gas emissions without compromising the driving performance and the driving range. This paper presents results showing how the positive fuel properties of natural gas can be fully utilised in a heavily downsized engine. The engine was modified to cope with the significantly higher mechanical and thermal loads when operating at high specific outputs on compressed natural gas. In this study, peak cylinder pressures of up to 180 bar and specific power output levels of 110 kW/l were realised. It is also shown that having cylinder components specific to natural gas can yield significant reductions in the fuel consumption and, in conjunction with a variable-geometry turbine, a port-fuelled compressed-natural-gas engine can achieve a impressive low-speed torque (a brake mean effective power of 2700 kPa at 1500 r/min) and good transient response characteristics. The results achieved from the test engine while operating on compressed natural gas are compared with measurements from the baseline gasoline-fuelled direct-injection engine. In addition, a comparison between port fuel injection and direct injection of compressed natural gas is presented. This also includes an investigation into the specific performance challenges presented by port-fuel-injected compressed natural gas. The potential carbon dioxide savings offered by this heavily downsized compressed-natural-gas engine, of up to 50% at peak power and 20–40% for the driving-cycle region (including real-driving-emissions testing), are presented and discussed.